[PP.03.11] INFLUENCE OF AGE ON THE RELATIONSHIP OF RENAL FUNCTION IMPAIRMENT WITH SYSTEMIC VASCULAR DAMAGE IN HYPERTENSION. (September 2017) - Geraci, G.; Mule', G.; Zammuto, M.; Mogavero, M.; Geraci, C.; Cottone, S.
Abstract : Objective: Aging is a strong predictor of cardiovascular events. Several studies showed that aging increased risk through progressive development of morphofunctional vascular changes. Moreover, renal impairment related to aging has also been suggested to explain the increased cardiovascular risk in elderly. Vascular impairment and kidney damage have been strongly associated each other, but they have different dynamics of progression over time, and it is not known if age changes the abovementioned relationship. The aim of this study is to evaluate, in hypertensive patients, the influence of age on the association between renal damage (glomerular filtration rate, albuminuria and renal resistance index (RRI)) with subclinical vascular damage (carotid intima-media thickness (cIMT) and aortic pulse wave velocity (aPWV)). Design and method: We enrolled 476 hypertensive subjects (30–90 years). The population was divided into 2 groups: subjects > 65 years (elderly hypertensives; n = 126) (EH) and subjects < 65 years (not elderly hypertensives; n = 350) (NEH). A Duplex ultrasonographic examination of both carotid and renal vasculature was performed in all patients. aPWV was assessed through oscillometric device. Results: EH had lower eGFR and higher albuminuria, RRI, cIMT and PWV compared to NEH (all p < 0.001). Age significantly correlated with eGFR, albuminuria, RRI, cIMT and aPWV in the entire study population (all p < 0.001) and in the two subgroups divided by age. In EH group, as well as in NEH group, cIMT was strongly associated with eGFR and RRI (p < 0.01), but not with albuminuria. In contrast, aPWV significantly correlated with all indices of renal damage (eGFR and albuminuria: p < 0.001; RRI: p < 0.01) in NEH, whereas it showed significant association only with eGFR in EH (p < 0.001). The cIMT independently correlated with RRI and eGFR in NEH, whereas it was significantly related only to RRI in EH. aPWV was independently associated with albuminuria in NEH, whereas it did not independently correlate with any indices of renal damage in EH. Conclusions: Age is an important modifier of the relationships between renal damage (eGFR, albuminuria and RRI) subclinical vascular involvement (cIMT and aPWV).